Investigating the potentialities of Monte Carlo simulation for assessing soil water content via proximal gamma-ray spectroscopy. (December 2018) - Baldoncini, Marica; Albéri, Matteo; Bottardi, Carlo; Chiarelli, Enrico; Raptis, Kassandra Giulia Cristina; Strati, Virginia; Mantovani, Fabio
Abstract: Proximal gamma-ray spectroscopy recently emerged as a promising technique for non-stop monitoring of soil water content with possible applications in the field of precision farming. The potentialities of the method are investigated by means of Monte Carlo simulations applied to the reconstruction of gamma-ray spectra collected by a NaI scintillation detector permanently installed at an agricultural experimental site. A two steps simulation strategy based on a geometrical translational invariance is developed. The strengths of this approach are the reduction of computational time with respect to a direct source-detector simulation, the reconstruction of 40 K, 232 Th and 238 U fundamental spectra, the customization in relation to different experimental scenarios and the investigation of effects due to individual variables for sensitivity studies. The reliability of the simulation is effectively validated against an experimental measurement with known soil water content and radionuclides abundances. The relation between soil water content and gamma signal is theoretically derived and applied to a Monte Carlo synthetic calibration performed with the specific soil composition of the experimental site. Ready to use general formulae and simulated coefficients for the estimation of soil water content are also provided adopting standard soil compositions. Linear regressions between input and output soil water contents, inferred from simulated 40 K and 208 Tl gamma signals, provide excellent results demonstrating the capability of the proposed method in estimating soil water content with an average uncertainty <1%. Highlights: Proximal γ-ray spectroscopy has extraordinary sensitivity to soil water content. A two-steps Monte Carlo method based on a translational invariance is developed. The 40 K, 238 U and 232 Th fundamental spectra of a permanent γ-station are simulated. Ready to use formulae are provided for estimating soil water content from γ-signal. Excellent linear regressions between input and output soil moistures are obtained.